Optimizing Problem-Solving Skills in Pedagogical Content Knowledge for Prospective Madrasah Ibtidaiyah Teachers - Silviana Nur Faizah; Lia Yuliati; Riska Pristiani (Nazhruna: Jurnal Pendidikan Islam, 2025)
Problem-solving competence is crucial for prospective Madrasah Ibtidaiyah teachers in making instructional decisions. This study examined the influence of project-based learning on problem-solving skills within Pedagogical Content Knowledge (PCK) and identified supporting and inhibiting factors in a civic education instruction course. An embedded mixed-method design was applied to 46 prospective Madrasah Ibtidaiyah teachers at Universitas Islam Lamongan. Quantitative data were gathered through the Problem-Solving Inventory and problem-solving skills within the PCK test dimension. These data were analyzed using the Wilcoxon Signed Rank Test, effect size, and N-gain. Qualitative data from observations, interviews, and documentation were thematically analyzed. Results indicated that project-based learning significantly enhanced problem-solving skills (p = 0.000), with a medium effect size (0.697) on the Problem Solving Inventory and a large effect size (0.87) on PCK. However, the N-gain score was relatively low (0.27). Qualitative findings reinforced these results, highlighting contextual learning, collaboration, critical thinking, systematic planning, reflection, lecturer support, resource availability, and field experience as enablers. At the same time, group dynamics, coordination with school teachers, and students’ initial readiness acted as barriers. This study underscores the potential of project-based learning to bridge theory and practice while fostering problem-solving skills among prospective Madrasah Ibtidaiyah teachers. Its novelty lies in exploring project-based learning across planning, implementation, and reflection, which represent enacted PCK (ePCK) within the Refined Consensus Model, as well as integrating collective PCK (cPCK) as content knowledge. Future research should involve larger samples, design project-based pedagogical modules, and examine long-term effects on both ePCK and cPCK development.